Prevalence and susceptibility of Saccharomyces cerevisiae causing vaginitis in Greek women - Papaemmanouil, V.; Georgogiannis, N.; Plega, M.; Lalaki, J.; Lydakis, D.; Dimitriou, M.; Papadimitriou, A. (Anaerobe, 2011)
Saccharomyces cerevisiae is an ascomycetous yeast, that is traditionally used in wine bread and beer production. Vaginitis caused by S. cerevisiae is rare. The aim of this study was to evaluate the frequency of S. cerevisiae isolation from the vagina in two groups of women and determined the in vitro susceptibility of this fungus. Vaginal samples were collected from a total of262 (asymptomaticandsymptomatic) women with vaginitis attending the centre of family planning of General hospital ofPiraeus. All blastomycetes that isolated from the vaginal samples were examined for microscopic morphological tests and identified by conventional methods: By API 20 C AUX and ID 32 C (Biomerieux). Antifungal susceptility testing for amphotericin B,fluconazole itraconazole,voriconazole, posaconazole and caspofungin was performed by E -test (Ab BIODIKS SWEDEN) against S. cerevisiae. A total of 16 isolates of S. cerevisiae derived from vaginal sample of the referred women, average 6.10%. Susceptibility of 16 isolates of S. cerevisiae to a variety of antimycotic agents were obtained. So all isolates of S. cerevisiae were resistant to fluconazole, posaconazole and intraconazole, but they were sensitive to voriconazole caspofungin and Amphotericin B which were found sensitive (except 1/16 strains). None of the 16 patients had a history of occupational domestic use of baker’s yeast. Vaginitis caused by S. cerevisiae occur, is rising and cannot be ignored. Treatment of Saccharomyces vaginitis constitutes a major challenge and may require selected and often prolonged therapy.